Tip and taper compatibility of accessory gutta-percha points with rotary and reciprocating instruments - Streck, Júlia Niero Zanatta; Arcaro, Sabrina; Ceretta, Renan Antônio; Bortoluzzi, Eduardo Antunes; Garcia, Lucas da Fonseca Roberti; de Almeida, Josiane; Kopper, Patrícia Maria Poli; Bernardi, Anarela Vassen (Restorative dentistry & endodontics, 2023)
This study was conducted to evaluate and compare the tip and taper compatibility of accessory gutta-percha points (AGPs) with various rotary and reciprocating instruments.ObjectivesThis study was conducted to evaluate and compare the tip and taper compatibility of accessory gutta-percha points (AGPs) with various rotary and reciprocating instruments.Using a profile analyzer, tip and taper measurements were taken of 10 AGPs of each of the 14 models available from Odous de Deus and the 4 models available from Dentsply-Maillefer. Diameter measurements were taken at 1-mm intervals, from 3 mm from the tip (D3) to 16 mm.Materials and MethodsUsing a profile analyzer, tip and taper measurements were taken of 10 AGPs of each of the 14 models available from Odous de Deus and the 4 models available from Dentsply-Maillefer. Diameter measurements were taken at 1-mm intervals, from 3 mm from the tip (D3) to 16 mm.Based on the mean values obtained, 3-dimensional (3D) models of the AGPs were drawn in Autodesk Fusion 360 and superimposed on 3D models of each instrument selected (Mtwo, Reciproc, RaCe, K3, and ProDesign Logic) to determine the compatibility between the instrument and the AGP. Data corresponding to the tips and tapers of the various AGPs, as well as the tip and taper differences between the AGPs and the instruments, were analyzed using descriptive statistics. The tapers of the AGPs were subject to the American National Standards Institute/American Dental Association No. 57 standard. The Odous de Deus extra-long medium and extra-long extra-medium AGPs were shown to be compatible with Mtwo, K3, and ProDesign Logic instruments with taper 0.06 and tip sizes 25 and 30, while the Dentsply fine and fine medium cones were compatible with Mtwo, RaCe, and K3 instruments with conicity of 0.04 and tip sizes 35 and 40.ResultsBased on the mean values obtained, 3-dimensional (3D) models of the AGPs were drawn in Autodesk Fusion 360 and superimposed on 3D models of each instrument selected (Mtwo, Reciproc, RaCe, K3, and ProDesign Logic) to determine the compatibility between the instrument and the AGP. Data corresponding to the tips and tapers of the various AGPs, as well as the tip and taper differences between the AGPs and the instruments, were analyzed using descriptive statistics. The tapers of the AGPs were subject to the American National Standards Institute/American Dental Association No. 57 standard. The Odous de Deus extra-long medium and extra-long extra-medium AGPs were shown to be compatible with Mtwo, K3, and ProDesign Logic instruments with taper 0.06 and tip sizes 25 and 30, while the Dentsply fine and fine medium cones were compatible with Mtwo, RaCe, and K3 instruments with conicity of 0.04 and tip sizes 35 and 40.Both the Odous de Deus and Dentsply commercial brands included 2 AGP models with tip (D3) and taper compatibility with Mtwo, RaCe, K3, and/or Prodesign Logic instruments.ConclusionsBoth the Odous de Deus and Dentsply commercial brands included 2 AGP models with tip (D3) and taper compatibility with Mtwo, RaCe, K3, and/or Prodesign Logic instruments.